CGRP outflow into jugular blood and cerebrospinal fluid and permeance for CGRP of rat dura mater - Risch, Miriam; Vogler, Birgit; Dux, Maria; Meßlinger, Karl (Journal of Headache and Pain, 2021)
Background: Calcitonin gene-related peptide (CGRP) is released from activated meningeal afferent fibres in the cranial dura mater, which likely accompanies severe headache attacks. Increased CGRP levels have been observed in different extracellular fluid compartments during primary headaches such as migraine but it is not entirely clear how CGRP is drained from the meninges. Methods: We have used an in vivo preparation of the rat to examine after which time and at which concentration CGRP applied onto the exposed parietal dura mater appears in the jugular venous blood and the cerebrospinal fluid (CSF) collected from the cisterna magna. Recordings of meningeal (dural) and cortical (pial) blood flow were used to monitor the vasodilatory effect of CGRP. In a new ex vivo preparation we examined how much of a defined CGRP concentration applied to the arachnoidal side penetrates the dura. CGRP concentrations were determined with an approved enzyme immunoassay. Results: CGRP levels in the jugular plasma in vivo were slightly elevated compared to baseline values 5-20 min after dural application of CGRP (10 μM), in the CSF a significant three-fold increase was seen after 35 min. Meningeal but not cortical blood flow showed significant increases. The spontaneous CGRP release from the dura mater ex vivo was above the applied low concentration of 1 pM. CGRP at 1 nM did only partly penetrate the dura. Conclusions: We conclude that only a small fraction of CGRP applied onto the dura mater reaches the jugular blood and, in a delayed manner, also the CSF. The dura mater may constitute a barrier for CGRP and limits diffusion into the CSF of the subarachnoidal space, where the CGRP concentration is too low to cause vasodilatation.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Calcitonin gene-related peptide; Cerebrospinal fluid; Jugular plasma; Meningeal blood flow; Primary headaches